Membedah Anatomi Kejahatan Terorganisir: Studi Putusan Permufakatan Jahat di Era Digital - Kurniawan Kurniawan; Khaerul Mannan; Muammad Darwis (Jurnal Litigasi Amsir, 2024)
This study aims to analyze malicious consensus in narcotics cases in verdict number 101/Pid.Sus/2020/PN. Pre and the consideration of the panel of judges in imposing the sentence. Using normative research methods, this study examines legal norms, principles, theories, and legal arguments related to the case. The results of the analysis show that the defendant is legally and convincingly proven guilty of committing the crime of "without rights or against the law, carrying out an attempt or malicious conspiracy to commit a criminal act of narcotics and a precursor, namely possessing, storing, possessing, or providing Class I narcotics that are not plants" as contained in the Narcotics Law. The panel of judges considered that the defendant was responsible for his actions because when committing the crime, the defendant was in physical and spiritual health and was aware of the impact of his actions.